L’excès dans la fiction de Wilkie Collins - Françoise Dupeyron-Lafay (Cahiers Victoriens et Edouardiens, 2006)
Excess is omnipresent in Wilkie Collins’s novels, but this paper will focus on Basil (1852), No Name (1862), The Moonstone (1868), Man and Wife (1870) and The Law and The Lady (1875). Actually, the modes and manifestations of excess cannot be limited to extrovert behaviour, unbridled passions, and all types of gothic violence. In these works, some of the reserved and unobtrusive female characters that embody excess « err » on the side of introversion, retreat into silence and illness and become almost « invisible ». This policy of self-censorship, and excessive somatization, gives a symptomatic function to excess as a revelator of social pathologies (unfair patriarchal laws) and family disorders — repressive and unhealthy marital situations and all forms of abuse inflicted on wives. All these variations on the gothic pattern of persecution enacted in « the secret theatre of home » serve to expose and denounce social and family diseases.Physical and mental disease is of course a central concern for two major male (though sexually ambiguous) Collinsian figures, namely Ezra Jennings in The Moonstone—an opium (ab)user like Thomas De Quincey (a strong influence in the novel) and like Collins himself—and Miserrimus Dexter (associated with a Romantic intertext of excess) in The Law and The Lady. Paradoxically, the resolution of both (detective) novels, the return to order and normality are finally achieved thanks to Jennings (a sick and ostracized doctor) and Dexter (a crippled amateur artist threatened with incurable madness). Both men are ill, marginal, stand for eccentricity and excess, and occasionally act as Collins’s mouthpieces, too.The writer’s ironic and subversive use of these characters to promote « happy endings » may therefore be regarded as another kind of excess.